Efforts to Prevent the Increase in Child Marriage in Loloan Hamlet, Loloan Village, Bayan District in 2024 - Afrianti, Jina; Hariani, Riska; Sumiadi, Raden; Warni, Sitrani; Andani, Novia; Wijaya, Pema (Jurnal Ilmiah Mandala Education (JIME), 2024)
The purpose of writing this article is to examine or describe efforts to prevent the increase in child marriage in Loloan Village, Bayan District. The type of research used in this research is qualitative research using interview and observation methods, with information from children, village heads and participants from local residents. The results obtained from this qualitative research show efforts to prevent the increase in child marriage. The efforts made by researchers include conducting outreach or providing regular views to children aged 12 to 20 years regarding child marriage. by holding outreach activities related to child marriage, this is a work program carried out by researchers in Loloan Village, Bayan District involving the school and students at SMPN 4 Bayan and Mts Miftahussuar NW Loloan class 9.